2000
DOI: 10.1108/eum0000000005382
|View full text |Cite
|
Sign up to set email alerts
|

Agency costs and corporate control devices in the Turkish manufacturing industry

Abstract: Documents evidence on the interdependence between the mechanisms used to control the agency costs in Turkish manufacturing firms where the external control devices are restricted and most of the firms have concentrated ownership. The ownership concentration, board size and composition, managerial shareholdings, institutional shareholdings, and family shareholdings are the selected devices. Evidence reveals that the proportion of insiders on the board is positively related to the percentage of family shareholdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 56 publications
1
27
0
2
Order By: Relevance
“…Berle and Means developed a dichotomy of ownership and identified two types namely, Owner-controlled firms and Managerially-controlled firms. McEachern found it to be insufficient for explanation of ownership structure and its impacts, so he identified three types adding Externallycontrolled firms (cited by Ugurlu, 2000) (i) Owner controlled firms are the ones where the managers are the dominant shareholders. (ii) Externally controlled firms are the ones where the managers are not dominant shareholders.…”
Section: Ownership Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Berle and Means developed a dichotomy of ownership and identified two types namely, Owner-controlled firms and Managerially-controlled firms. McEachern found it to be insufficient for explanation of ownership structure and its impacts, so he identified three types adding Externallycontrolled firms (cited by Ugurlu, 2000) (i) Owner controlled firms are the ones where the managers are the dominant shareholders. (ii) Externally controlled firms are the ones where the managers are not dominant shareholders.…”
Section: Ownership Structurementioning
confidence: 99%
“…Through greater monitoring the negative and positive impacts of ownership concentration can be equated, and some time benefits can over weigh the negativities (Kaserer and Moldenhauer, 2008). Insider ownership is negatively related to foreign institutional ownership (Ugurlu, 2000).…”
Section: Ownership Structurementioning
confidence: 99%
See 1 more Smart Citation
“…This suggests a possible negative impact on firm performance. Ugurlu (2000), in an earlier study, came to similar conclusions in a study of Turkish manufacturing firms. Gomez‐Mejia, Haynes, Nunez‐Nickel, Jacobson, and Moyano‐Fuentes (2007) found this pattern on inconsistencies in their study of 1,237 family owned Spanish olive mills and concluded that “family firms may be risk willing and risk averse at the same time” (p. 106).…”
Section: Previous Researchmentioning
confidence: 99%
“…Empirical studies on family-controlled businesses have not provided the needed evidence to resolve this theoretical debate. Entrenchment theory has been applied to insider ownership and firm performance in large publicly traded companies, but has seldom been used to explain that same relationship in the context of family businesses (Hu and Kumar 2004;Ugurlu 2000;Wright et al 1996). On the other hand, agency theory has generated inconsistent result in studies when applied to familycontrolled businesses (Lee 2004;Yammeesri and Lodh 2004;Anderson and Reeb 2003;McConaughy, Matthews, and Fialko 2001).…”
Section: Introductionmentioning
confidence: 99%